Current Research on HIV Drug Resistance - Ji, Hezhao (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
HIV drug resistance is an unavoidable challenge for HIV/AIDS professionals, and it has long been a major obstacle hindering the global effort to contain HIV/AIDS. Pathogens journal launched a topical collection in 2021 on "Current Research on HIV Drug Resistance", aiming to catch the latest advancements in HIV resistance diagnosis, surveillance and research. This book compiles all articles published in this collection, combining original research and review articles on HIV drug resistance.